SCIENTIFIC VIEWS IN THE STUDY OF MUQIMI'S LIFE AND WORK - Shakhnoza Said kizi, Bakhshillaeva (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2022)
In world literature, a number of scientific investigations are being conducted on the classification of irony, its artistic manifestations, parody, paradox, grotesque and image. The role of irony and image in the structure of the work of art in the world of literary science, in which the coverage and identification of the individual skills of the writer remains one of the urgent tasks. In modern Uzbek literature, there is an approach based on various research methods of world literature in the analysis of works of art, the coverage of the poetic skills of the author.